2010
DOI: 10.1016/j.neuroimage.2010.04.262
|View full text |Cite
|
Sign up to set email alerts
|

Sparsely-distributed organization of face and limb activations in human ventral temporal cortex

Abstract: Functional magnetic resonance imaging (fMRI) has identified face- and body part-selective regions, as well as distributed activation patterns for object categories across human ventral temporal cortex (VTC), eliciting a debate regarding functional organization in VTC and neural coding of object categories. Using high-resolution fMRI, we illustrate that face- and limb-selective activations alternate in a series of largely nonoverlapping clusters in lateral VTC along the inferior occipital gyrus (IOG), fusiform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
296
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 267 publications
(344 citation statements)
references
References 67 publications
(110 reference statements)
45
296
2
1
Order By: Relevance
“…Substantial evidence suggests faces are processed by mechanisms that are not involved in the recognition of most other objects (19,(30)(31)(32)(33)(34)(35), but whether these mechanisms are Although it has been suggested that the response time comparison in the verification trials is the critical measure of expertise, we have empirical and theoretical concerns about it. In one of the first papers involving greebles (13), of 12 subjects, two met the expertise criterion in the fourth session, two in the third session, one in the second session, and one in the first session.…”
Section: Implications For the Specificity Of The Mechanisms Used Formentioning
confidence: 89%
“…Substantial evidence suggests faces are processed by mechanisms that are not involved in the recognition of most other objects (19,(30)(31)(32)(33)(34)(35), but whether these mechanisms are Although it has been suggested that the response time comparison in the verification trials is the critical measure of expertise, we have empirical and theoretical concerns about it. In one of the first papers involving greebles (13), of 12 subjects, two met the expertise criterion in the fourth session, two in the third session, one in the second session, and one in the first session.…”
Section: Implications For the Specificity Of The Mechanisms Used Formentioning
confidence: 89%
“…Sex categorization times on correct trials did not differ across the three types of dyads [F(2,22) = .24, p = .79]. Rossion et al, 2012;Weiner & Grill-Spector, 2010) and replicate reports according to which face-selective activity is right-lateralized and elicited more consistently in the FFA than the OFA (e.g., Andrews, Davies-Thompson, Kingstone, & Young, 2010;Engell & McCarthy, 2013;. Mean parameter estimates in all five ROIs were extracted from the main experiment for each participant (see Figure 3).…”
Section: Behavioral Analysismentioning
confidence: 99%
“…Such encoding is thought to occur in the so-called core neural network of person perception (Gobbini & Haxby, 2007;Rossion, Hanseeuw, & Dricot, 2012;Weiner & Grill-Spector, 2010), a system that comprises several brain regions, including the occipital face area (OFA), fusiform face area (FFA), posterior superior temporal sulcus (pSTS), extrastriate body area (EBA) and fusiform body area (FBA). All five regions act in concert to extract the structural and dynamic representation of an individual's facial and bodily appearance (Grosbras, Beaton, & Eickhoff, 2012;Gobbini & Haxby, 2007;Pavlova, 2012;Peelen & Downing, 2007;Weiner & Grill-Spector, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are discussed in terms of motor processes in the left brain hemisphere associated with action nouns. Weiner and Grill-Spector (2012) summarize the results of two recently published studies (Weiner & Grill-Spector, 2010 that investigated the distribution of face and limb selectivity in human visual cortex. They propose a new three-stream model of high-level visual cortex which includes ventral, lateral and dorsal areas where multimodal processing related to vision, action and language might converge.…”
Section: Content Of the Special Issuementioning
confidence: 99%